2011
DOI: 10.1165/rcmb.2010-0075oc
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Function of the IL-1 Family Cytokine IL-1F9 in Human Bronchial Epithelial Cells

Abstract: The IL-1 family of cytokines, which now includes 11 members, is well known to participate in inflammation. Although the most recently recognized IL-1 family cytokines (IL-1F5-11) have been shown to be expressed in airway epithelial cells, the regulation of their expression and function in the epithelium has not been extensively studied. We investigated the regulation of IL-1F5-11 in primary normal human bronchial epithelial cells. Messenger (m)RNAs for IL-1F6 and IL-1F9, but not IL-1F5, IL-1F8 or IL-1F10, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
155
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(172 citation statements)
references
References 41 publications
16
155
0
1
Order By: Relevance
“…and CCL20, and cytokines IL-6, G-CSF, and GM-CSF, which can recruit and activate DC, macrophages, neutrophils, T cells, and NK cells. Studies in other epithelial tissues, such as human bronchial epithelial cells and mouse lungs, showed that IL-36, particularly IL-36g, induces the neutrophil-attracting chemokines IL-8 and CXCL1, the T cell-attracting chemokines CXCL10, and the DC-attracting and Th17-attracting chemokine CCL20, as well as cytokines and growth factors, including IL-6, G-CSF, and GM-CSF (35,36). Data from previous studies combined with our data indicate that IL-36g would activate epithelial cells to induce chemokines and recruit inflammatory cells for the initial stages of innate immunity in skin inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…and CCL20, and cytokines IL-6, G-CSF, and GM-CSF, which can recruit and activate DC, macrophages, neutrophils, T cells, and NK cells. Studies in other epithelial tissues, such as human bronchial epithelial cells and mouse lungs, showed that IL-36, particularly IL-36g, induces the neutrophil-attracting chemokines IL-8 and CXCL1, the T cell-attracting chemokines CXCL10, and the DC-attracting and Th17-attracting chemokine CCL20, as well as cytokines and growth factors, including IL-6, G-CSF, and GM-CSF (35,36). Data from previous studies combined with our data indicate that IL-36g would activate epithelial cells to induce chemokines and recruit inflammatory cells for the initial stages of innate immunity in skin inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in both mice and humans show that these cells produce large amounts of IL-5 and IL-13 in the presence of the epithelial cell-derived cytokines thymic stromal lymphopoietin (TSLP), IL-25, IL-33 (70), and prostaglandin D2 (PGD2) (71,72). The release of these cytokines is induced by proteases, which are present in various allergens (73), as well as viruses, including rhinovirus, and bacteria, such as staphylococcus, which have been associated with asthma exacerbations and chronic sinusitis (74,75). Since approximately 25% of patients with severe asthma do not display atopy (at least to known allergens), it is possible that there are other environmental triggers that induce a type 2 response without invoking a Th2 response.…”
Section: A Role For Innate Type 2 Immunitymentioning
confidence: 99%
“…Primary normal human bronchial epithelial (NHBE; Lonza, Walkersville, MD) cells, from at least three different donors, were plated in 12-well culture plates and either grown in submerged or in air-liquid interface conditions, as previously described (34). NHBE cells were deprived of hydrocortisone and growth factors from the media for 24 hours before stimulation.…”
Section: Cell Culture Treatments and Transfectionmentioning
confidence: 99%
“…Real-time RT-PCR was performed with the TaqMan method using an Applied Biosystems 7,500 sequence detection system (Life Technologies, Grand Island, NY) as described previously (34). The levels of expression of mRNA were normalized to the housekeeping gene, b-actin, and results were analyzed by quantifying the absolute amount of mRNA.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%